Spark Plasma Sintering tool design for preparing alumina-based Functionally Graded Materials. Issue 2 (1st February 2016) - Morin, C.; Le Gallet, S.; Ariane, M.; Bernard, F.
Abstract: A way to produce Functionally Graded Materials (FGM) is by means of Spark Plasma Sintering (SPS) and specifically designated tools. These new tools permit a current density modulation and therefore a temperature variation along the z -axis. The key feature relies on a varying die section. FEM modelling has given the suitable range of die dimensions between the top and the bottom to obtain a given temperature gradient (around 300 °C) out of roughly a 15 mm height. Experiments conducted in different configurations (with or without samples) and the measurement of the associated thermal gradient led to improvements of the mould (in particular the introduction of a counter-piston). By the use of this specific mould, an alumina showcasing a microstructure gradient was sintered: from a dense face exhibiting 1.3 µm grains to a porous one composed of 200 nm grains.